ARID1A silencing-mediated upregulation of microRNA-652 accelerates cigarette smoke-induced human bronchial epithelial cell transformation by targeting ZFAND5 - Kang-liang Zhang; Dan-ni Wu; Rui-heng Chen; Chong Zheng; Ri-sheng Huang; Xiao-dan Zhao (BMC Pulmonary Medicine)
Abstract Cigarette smoking is an important risk factor in lung cancer development. As a class of regulatory RNAs, microRNAs (miRs) participate in various biological processes. In the present study, we searched for the key miRs that mediate cigarette smoke-induced aggressive phenotype in human bronchial epithelial (HBE) cells. Our results demonstrated that miR-652 was upregulated in cigarette smoke extract (CSE)-exposed HBE cells. ARID1A silencing due to hypermethylation of its promoter accounted for the upregulation of miR-652 in CSE-treated HBE cells. Overexpression of miR-652 accelerated the proliferation, migration, and anchorage-independent growth of HBE cells exposed to CSE. Knockdown of miR-652 attenuated the growth and migration of CSE-treated HBE cells. According to bioinformatic prediction and luciferase reporter assays, ZFAND5 was found to be a target of miR-652. Overexpression of miR-652 suppressed the protein expression of ZFAND5 in HBE cells, without altering its mRNA abundance. CSE treatment reduced the protein expression of ZFAND5 in HBE cells. Depletion of ZFAND5 potentiated the anchorage-independent growth and migration of CSE-treated HBE cells. Enforced expression of ZFAND5 reversed miR-652-mediated enhancement of anchorage-independent growth and migration in CSE-treated HBE cells. In conclusion, miR-652 potentiates CSE-induced aggressive phenotype in HBE cells by repressing ZFAND5 protein expression. The potential involvement of miR-652 in cigarette smoking-related lung carcinogenesis warrants further investigation.